19th-CENTURY LABOR MONEY SCHEMES, SELF-REALIZATION THROUGH LABOR, AND THE UTOPIAN IDEA. (1st July 2012) - Hauhart, Robert C.
Abstract : In 19th-century European socialist political economic theory, the money system was widely viewed by reformers as the root of social evil. Robert Owen (1771-1858) and Joseph Proudhon (1809-1865), among others, proposed replacing existing money systems with a currency based on labor time instead. This type of social scheme, which tried to reform both social labor and economic relations by introducing equitable labor exchange, was called "labor money" and became popular among 19th-century European Utopian socialists. Often, equitable labor exchange programs were joined with the idea of self-realization through work in proposals for Utopian communities. While the "labor money" concept has only enjoyed modest intellectual, political, or economic life over the last 150 years, the idea is revived periodically by those seeking a more cooperative way of life. In the 1980s Dr. Edgar Cahn wrote a book proposing "time dollar" exchange programs and a labor credit system is at the heart of the United States' most successful secular intentional community, Twin Oaks Community, Louisa, Virginia.